Gender Identity and Cosplayer Stigmation In Malang City - Dita Wahyu Putri Muzdaliva; Siti Kholifah; Intan Rahmawati (Wacana Journal of Social and Humanity Studies, 2021)
The purpose of this research is to examine gender identity and the stigma experienced by cosplayers in Malang City. A gender identity that is formed through repeated actions in cosplay life. A cosplayer has a different gender between social life and life when becoming a cosplayer. Gender differences that are owned by cosplayers raise problems in the form of stigma. The stigma that emerges and attaches to cosplayers who cross-gender is in the form of sexual deviance. The research method used in the research is descriptive qualitative with the resulting data in the form of written or spoken words from people and observable behavior. Data collection used is observation, interview, and documentation. The result of this research is that the gender identity of cosplayers is formed through actions that display gender that is repeated in cosplay life and continuously. A cosplayer displays his gender to imitate the character or character he likes. Second, the stigma that appears in cosplayer life is due to gender differences between social life and life as a cosplayer. The existence of gender differences causes cosplayers to get the stigma of sexual deviance.